CID-6033590 inhibits p38MAPK pathway and induces S-phase cell cycle arrest and apoptosis in DU145 and PC-3 cells. (October 2019) - Sharma, Guru Prasad; Gurung, Sumiran Kumar; Inam, Afreen; Nigam, Lokesh; Bist, Archana; Mohapatra, Debasish; Senapati, Shantibhusan; Subbarao, Naidu; Azam, Amir; Mondal, Neelima
Abstract: Metastatic prostate cancer, with no effective treatment, is among the leading causes of cancer-associated deaths in men. Overexpression of p38αMAPK has been observed in neuroendocrine prostate cancer patients and in both DU145 and PC-3 cell lines and represents a good drug target. Sulfonamide derivatives have shown biological activities against many human diseases, including cancer. CID-6033590, a sulfonylhydrazide compound, screened from PubChem database by molecular docking with p38αMAPK, was evaluated for anti-cancerous activities. CID-6033590 induced toxicity in both DU145 and PC-3 cells in a concentration and time-dependent manner with an IC50 value of 60 μM and 66 μM, respectively. Sub-cytotoxic concentrations of the compound significantly induced S-phase cell cycle arrest, inhibited cyclinA/CDK2 complex and blocked cell proliferation. Further, CID-6033590 downregulated phosphorylation of p38MAPK (P-p38) as well as its downstream targets, Activating transcription factor 2 (ATF-2) and Heat shock protein 27 (Hsp27). The compound increased ROS and decreased mitochondrial membrane potential (Δψm), downregulated Bcl-2 and survivin and cleaved poly ADP ribose polymerase (PARP) and caspase-3, indicating the induction of apoptosis. The evaluaion of the compound on noncancerous, human prostatic epithelial cell line RWPE-1, and healthy murine tissues yielded no significant toxicity. Taken together, we suggest CID-6033590 as a potential candidate for prostate cancer therapy. Highlights: In-silico screening and docking data indicated that CID-6033590 inhibited p38MAPK. CID-6033590 exhibited IC50 value of 60μM and 66μM in prostate cancer cell lines DU145 and PC-3 respectively. 10μM CID-6033590 inhibited cyclin A/Cdk2 activity, induced proteasomal degradation of PCNA and arrested cells at S-phase. 10 μM CID-6033590 induced BRCA1 and p21, inhibited p38MAPK signal transduction pathway and induced apoptosis. Healthy tissues in mice were unaffected by CID-6033590 treatment.